2016
DOI: 10.1038/srep34051
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Early bace-1 and Global DNA Demethylation by S-Adenosylmethionine Reduces Amyloid Pathology and Improves Cognition in an Alzheimer’s Model

Abstract: General DNA hypomethylation is associated with Alzheimer’s disease (AD), but it is unclear when DNA hypomethylation starts or plays a role in AD pathology or whether DNA re-methylation would rescue early amyloid-related cognitive impairments. In an APP transgenic mouse model of AD-like amyloid pathology we found that early intraneuronal amyloid beta build-up is sufficient to unleash a global and beta-site amyloid precursor protein cleaving enzyme 1 (bace-1) DNA demethylation in AD-vulnerable brain regions. S-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 74 publications
4
42
0
Order By: Relevance
“…40 In line with these results, a correlation study demonstrated hypomethylation in the BACE1 promoter, with the methylation level of one CpG negatively correlated to the Aβ load, whereas the methylation level of another CpG was correlated to the rate of cognitive decline in AD patients. 37 Such findings support the reduction of BACE1 methylation in AD may possibly contribute to the accumulation of Aβ and the severity of disease progression. Presenilin 1 (PSEN1), another gene of interest in AD pathology, encodes one of the core proteins of γ-secretase that is responsible for the final cleavage of Aβ from APP.…”
Section: Amyloidogenic Pathwaysupporting
confidence: 61%
See 2 more Smart Citations
“…40 In line with these results, a correlation study demonstrated hypomethylation in the BACE1 promoter, with the methylation level of one CpG negatively correlated to the Aβ load, whereas the methylation level of another CpG was correlated to the rate of cognitive decline in AD patients. 37 Such findings support the reduction of BACE1 methylation in AD may possibly contribute to the accumulation of Aβ and the severity of disease progression. Presenilin 1 (PSEN1), another gene of interest in AD pathology, encodes one of the core proteins of γ-secretase that is responsible for the final cleavage of Aβ from APP.…”
Section: Amyloidogenic Pathwaysupporting
confidence: 61%
“…36 Screening of the global DNA methylation level in different brain regions in this mouse model corresponded with the spatial pattern of Aβ pathology. 37 Immunofluorescence colabeling was used to compare 5mC levels in regions affected by Aβ, which further confirmed a severe reduction of neurons compared with the total cell population, implying that Aβ primarily acts on neurons to induce hypomethylation. 37 Taken together, the above findings provide growing evidence to support the involvement of Aβ in reducing global DNA methylation in the initial disease stage, and Aβ accumulation in later stages then further promotes neuronal DNA demethylation.…”
Section: Amyloidogenic Pathwaymentioning
confidence: 78%
See 1 more Smart Citation
“…Persichilli et al [198] reported a significant decrease of thiol levels when the B vitamindeficient diet was supplemented with SAMe + superoxide dismutase and superoxide dismutase alone [198]. In a recent study on the APP transgenic mouse model of AD-like amyloid pathology, Do Carmo et al [199] found that the early BACE-1 and global DNA demethylation were rescued by chronic administration of SAMe, which contributed to the reduction of amyloid pathology and the improvement in cognition function. In conclusion, these studies in AD support the rationale that it is possible to use SAMe to treat brain disorders with a plausible epigenetic mechanism.…”
Section: Same Treatment In Neurological Diseasesmentioning
confidence: 99%
“…Abnormal methylation occurred at the level of DNA and amino acid was concerned with neurological disability (Blanc and Richard, 2017; Long et al, 2017). Dysfunctional methylation of DNA was associated with neuroinflammation (Nicolia et al, 2017), and it has been recognized as a key regulator for many neurodegenerative diseases as well, including Alzheimer's disease (Do Carmo et al, 2016) and Parkinson's disease (Jowaed et al, 2010). In terms of amino acid methylation, abnormal methylation of amino acid disturbed cysteine/methionine metabolism.…”
Section: Introductionmentioning
confidence: 99%